Application of peripheral blood cytokine and immunoglobulin detection in ACTH therapy for the treatment of infantile spasms - Wang, Xiaocui; Huang, Qin; Wu, Lulu; Yang, Yang; Ye, Xiaofei; Yang, Bin (Frontiers in Pediatrics, 2024)
Objective: To investigate the levels of lymphocytes, immunoglobulins, and cytokines in children with infantile spasms (IS) before and after adrenocorticotropic hormone (ACTH) therapy, and to explore its application in evaluating ACTH's therapeutic effects on IS. From May to November 2022, 35 children with IS treated in our hospital were observed, along with 35 healthy children as a control group. The observation group received ACTH intramuscular injections for 2 weeks. Fasting venous blood was collected from both groups before and after ACTH therapy. Immunoglobulin levels (IgG, IgA, IgM) were measured by immunoturbidimetry; T cell subsets (CD3+, CD3+CD4+, CD3+CD8+), B cell subsets (CD3-CD19+, CD3-CD16+CD56+ NK cells) were detected by flow cytometry; cytokine levels (IL-1β, IL-2R, IL-6) were measured by ELISA. Comparisons were made pre- and post-therapy in the observation group and between the observation and control groups. Results: Pre-therapy, the observation group had higher IgG and IgM levels and lower IgA levels compared to the control group (p < 0.05). CD3-CD19+ B cells were increased, while CD3+ T cells and CD3+CD4+ T cells were decreased (p < 0.05). No significant changes were observed in CD3+CD8+ T cells, CD3-CD16+CD56+ NK cells, or CD3+CD4+/CD3+CD8+ ratios (p > 0.05). Cytokine levels (IL-1β, IL-2R, IL-6) were higher (p < 0.05). Post-therapy, IgG levels decreased significantly (p < 0.05), while IgA and IgM levels remained unchanged (p > 0.05). CD3+ T cells and CD3+CD4+ T cells increased, while CD3-CD16+CD56+ NK cells and CD3-CD19+ B cells decreased (p < 0.05). No significant changes were observed in CD3+CD8+ T cells or CD3+CD4+/CD3+CD8+ ratios (p > 0.05). Cytokine levels decreased significantly (p < 0.05). Conclusion: Children with IS exhibit immune dysfunction, and ACTH treatment alters serological immune indexes, suggesting that ACTH may control seizures by regulating immune dysfunction. Therefore, the therapeutic effects of ACTH on IS can be evaluated by measuring cytokine and immunoglobulin levels.